Effectiveness of hearing protection intervention on use of hearing protection devices among selected manufacturing workers in Selangor, Malaysia - Sam, Wei Yeng (2017)
Introduction: Industrial noise cause hearing loss (HL) and hearing impairment (HI) among workers. HL occurs when air conduction hearing threshold levels at different frequencies are ≥25dB. HI refers to ≥25dB shift for average hearing threshold level at 0.5-3k Hz compare to standard audiometric reference level.Objective: Primary aim was to ascertain the effectiveness of hearing protection intervention to increase hearing protection devices use (HPDs) among selected manufacturing workers in Selangor. Methodology: A Solomon four-group study was conducted among 420 workers of 9 manufacturing companies in Selangor using multistage sampling method. Respondents were randomly assigned into 4 groups: pretested and non-pretested intervention or control groups. A total of 37 respondents (8.8%) were lost to follow-up. Intervention included preliminary walkthrough survey, noise monitoring, audiometric testing, intervention program with training video and manual specially designed for manufacturing settings and HPDs use demonstration. Main outcomes measured were hearing status, intention to use HPDs, predictors of HPDs use (perceived self-efficacy, outcome value, perceived barriers, perceived benefit, availability of HPDs, interpersonal influence, work climate and perceived stress), HPDs use in the workplace (HPDs workplace use) and during high noise exposure (HPDs high noise use). Questionnaires were adopted from selected scale of use of hearing protection questionnaires and were in English and Malay version. Data were collected at baseline and 3 months after intervention. Data analysis included multiple linear regressions (MLR) with adjustment on personal factors and series of analysis designated for Solomon four-group using Statistical Package for the Social Sciences (SPSS). Results: Prevalence for HL and HI was 73.3% and 23.3% respectively. More than 40% respondents suffered hearing problems at higher frequencies (4k and 6k Hz). HPDs use was correlated with perceived self-efficacy, interpersonal influence, perceived benefit, work climate, perceived barriers (p<.05). Age, gender, monthly income, education level, environmental noise exposure at home, work position, shift work, smoking status, sleep problem were related with hearing protection behaviour (p<.05), and were adjusted during MLR. Individually, MLR showed strongest predictors of HPDs workplace use was work climate, followed by interpersonal influence, perceived benefits, perceived self-efficacy, availability of HPDs and perceived barriers. Final model as a whole illustrated that significant predictors were perceived benefit and work climate. Perceived barriers and perceived benefits were significant predictors for HPDs high noise use, whereas for model as a whole, perceived barriers was the only significant predictor. Baseline mean HPDs workplace use was 38.1±31.8%, while baseline HPDs high noise use was 39.2±31.0%. Unexpectedly, 11.2% of respondents did not use HPDs at all. Based on short term outcome, intervention is effective in increasing HPDs workplace use and HPDs high noise use by 16.6% and 13.4% respectively. For immediate effect, score for intention to use HPDs before (70.0%) and after intervention (90.0%) were significantly different (p<.001). Intervention improved scores of perceived self-efficacy (3.4%), outcome value (4.4%), perceived barriers (-4.6%), perceived benefit (4.4%), interpersonal influence (4.2%) and work climate (3.3%). Conclusion: Hearing protection intervention developed served as an effective tool in increasing HPDs use among manufacturing workers for immediate and short term outcome through improving scores of predictors.